Inactivation of Mycobacterium tuberculosis for safe use outside of the BSL-3 laboratory - Watkins, Jackson, author; Dobos, Karen, advisor; Goodrich, Raymond, committee member; Slayden, Richard, committee member; Hall, Ed, committee member (Colorado State University. Libraries, 2020)
Techniques for pathogen inactivation have been long employed by research laboratories to help ease the financial, physical, and health strains associated with (A)BSL-3 work. While robust protocols exist for many of these techniques, there are many holes in research associated with characterization of damage to treated organisms, and standardized methods for comparative analysis of successful sterilization. The work in this thesis aimed to develop methods to better understand current techniques of inactivation. At the same time, it also aimed to characterize the limitations of both a novel approach to inactivation, as well as the pathogenic models we commonly use for infectious disease research. We accomplished this by first developing a D10 value and standardized curve to describe inactivation of Mycobacterium tuberculosis by traditional cesium irradiation techniques. D10 modeling is a stepping stone for comparative analysis of organisms to one another, and also maintains calibration potential to measure radioactive source decay over time. We then focused on the effect of riboflavin photochemistry on Mycobacterium smegmatis as a model for Mtb grown from large-scale culture. We demonstrated the potential for M. smegmatis to enter a viable but non-culturable state, as well as potential reluctance to readily uptake exogenous riboflavin, making it uniquely resistant to this specific method of photosensitizer damage. Characterization of damage to M. smegmatis through propidium iodide flow cytometry assays, and 8-oxoguanosine detection assays, also offered insight into the limitations of M. smegmatis as a model for Mtb.
Keywords: irradiation; riboflavin; inactivation; tuberculosis; photochemistry